2017
DOI: 10.3390/biology6020028
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Control of NRAMP1 (SLC11A1) Expression in Professional Phagocytes

Abstract: NRAMP1 (SLC11A1) is a professional phagocyte membrane importer of divalent metals that contributes to iron recycling at homeostasis and to nutritional immunity against infection. Analyses of data generated by several consortia and additional studies were integrated to hypothesize mechanisms restricting NRAMP1 expression to mature phagocytes. Results from various epigenetic and transcriptomic approaches were collected for mesodermal and hematopoietic cell types and compiled for combined analysis with results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 206 publications
(453 reference statements)
1
7
0
1
Order By: Relevance
“…The present study also identified a monocytic cell subset in porcine lymph nodes and tonsils characterized by high levels of CD14 expression, which clustered with monocytes and monocyte-derived macrophages in PCA, and expressed the monocyte/macrophage-specific lineage markers CD64 ( 53 ), CD68 ( 54 ) and SLC11A1 ( 55 ). The expression of ZFP36L1 , which is selectively upregulated during monocyte/macrophage differentiation ( 56 ), and the macrophage-specific transcription factors TFEC ( 57 ) and MAFB ( 58 ), together with CHIT1 , a gene involved in monocyte-to-macrophage differentiation ( 59 ), would indicate that this CD14 high population corresponds to monocyte-derived macrophages.…”
Section: Discussionsupporting
confidence: 58%
“…The present study also identified a monocytic cell subset in porcine lymph nodes and tonsils characterized by high levels of CD14 expression, which clustered with monocytes and monocyte-derived macrophages in PCA, and expressed the monocyte/macrophage-specific lineage markers CD64 ( 53 ), CD68 ( 54 ) and SLC11A1 ( 55 ). The expression of ZFP36L1 , which is selectively upregulated during monocyte/macrophage differentiation ( 56 ), and the macrophage-specific transcription factors TFEC ( 57 ) and MAFB ( 58 ), together with CHIT1 , a gene involved in monocyte-to-macrophage differentiation ( 59 ), would indicate that this CD14 high population corresponds to monocyte-derived macrophages.…”
Section: Discussionsupporting
confidence: 58%
“…NRAMP-1 triggers a non-immune response that works on the host cells and expressed on phagocytic cells (Cellier, 2017). NRAMP-1 functions to modulate cytocidal proteins that are toxic to the cells, such as bacterial cells and transmembrane conserving.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Egr2 gene may correlated with the HO-1 expression, which could convert heme to iron, and participated in memory, cognition and synaptic plasticity [56]. Furthermore, Egr2 may implicate in stimulating iron acquisition in pro-in ammatory conditions [57]. Consequently, we speculated that Egr2 may play a crucial role in cognitive function correlated to mitochondrial iron metabolism.…”
Section: Discussionmentioning
confidence: 95%